Influence of Drip-Irrigation Method on Performance and Yields of Cucumber and Tomato - Bajracharya, R.M.; Sharma, S. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
The conservation of water is crucial to sustainable agricultural production in areas of low rainfall or uneven precipitation distribution. Under such circumstances, drip irrigation methods offer a useful option for economic production of vegetable crops. This preliminary study examined the efficacy and performance of two drip irrigation methods on cucumber and tomato crops grown out of season. The initial results of the study indicated surface drip irrigation to give better establishment of the crop and higher yields than sub-surface drip method. Further work is needed, however, to establish the cause-effect relationships and actual viability of sub-surface drip irrigation method.